TINJAUAN YURIDIS TERHADAP DAMPAK HUKUM PELAKSANAAN PENGAMPUNAN PAJAK PENGHASILAN BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2016 TENTANG PENGAMPUNAN PAJAK (TAX AMNESTY) - Siti Norwahdahlia (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe purpose of the state contained in the preamble of the fourth paragraph of 1945 affirms national development. In order to improve the people’s welfare, the government strived to build the economy and the awareness and compliance of the community in the implementation and obligation to pay taxes as a source of state income collected by the government from the people used for national development. Tax amnesty is the abolition of taxes that should be payable, not subject to sanction of tax administration and criminal law in the field of taxation as regulated in law Number 11 Year 2016 About  Tax Amnesty. Tax amnesty is a privilege to be used or not by a taxpayer. Tax amnesty program is rare program that will not be given periodically.For the execution of tax amnesty is quite effective in exploring the potential of taxation in Indonesia, because in this way the taxpayer may disclose payment of income tax that has not been listed or underpay in annual notification.Keywords : Implementation of Income Tax Amnesty